Pengaruh Media Audio Visual Terhadap Hasil Belajar PKn Kelas III - Lestari, Nidya; Akhbar, M. Taheri; Dedy, Adrianus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Based on the results of observations, it was found that the learning process at SD Negeri 195 Palembang was the lack of media use so that students did not understand the material for theGaruda Pancasila symbol. Students have difficulty in understanding the material of the GarudaPancasila symbol and the learning media used are less effective, and the packaged learning systemis not yet attractive and optimal. The purpose of this study was to determine the effect of audiovisual media on the learning outcomes of third grade Civics at SD Negeri 195 Palembang. This research method uses a pre-experimental design method using a one group pretest-posttest design. The data collection technique used observation, test, and documentation, while the data analysis technique used the t test. Based on the results, it was found that the highest average test result was found in the final test (posttest) of 66.11, while the average for the initial test (prestest) was 48.29. Thus, there was an increase after the application of the influence of audio-visual media on the learning outcomes of third grade PKN students at SD Negeri 195 Palembang.